Institutions and structural unemployment: do capital-market imperfections matter? - Ansgar Belke; Rainer Fehn (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, Wirtschaftsordnung und Sozialpolitik, 2000)
This paper analyzes whether differences in institutional structures on capital markets contribute to explaining why some OECD-countries, in particular the Anglo-Saxon countries, have been much more successful over the last two decades in producing employment growth and in reducing unemployment than most continental-European OECD-countries. It is argued that the often-blamed labor-market rigidities alone, while important, do not provide a satisfactory explanation for these differences across countries and over time. Financial constraints are potentially important obstacles against creating new firms and jobs and thus against coping well with structural change and against moving successfully toward the "new economy". Highly developed venture capital markets should help to alleviate such financial constraints. This view that labor-market institutions should be supplemented by capitalmarket imperfections for explaining differences in employment performances is supported by our panel data analysis, in which venture capital turns out to be a significant institutional variable.
Keywords: E24; G24; 330; labor markets; unemployment; new economy; panel analysis; venture capital; Strukturelle Arbeitslosigkeit; Finanzmarkt; Unvollkommener Markt; Lohnrigidität; Arbeitsmarktflexibilisierung; Risikokapital; Beschäftigungseffekt; Schätzung; Theorie; OECD-Staaten